2020
DOI: 10.3390/antiox9111132
|View full text |Cite
|
Sign up to set email alerts
|

The Advanced Lipoxidation End-Product Malondialdehyde-Lysine in Aging and Longevity

Abstract: The nonenzymatic adduction of malondialdehyde (MDA) to the protein amino groups leads to the formation of malondialdehyde-lysine (MDALys). The degree of unsaturation of biological membranes and the intracellular oxidative conditions are the main factors that modulate MDALys formation. The low concentration of this modification in the different cellular components, found in a wide diversity of tissues and animal species, is indicative of the presence of a complex network of cellular protection mechanisms that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 140 publications
0
38
0
1
Order By: Relevance
“…This was reported in cows [ 63 ] and lysine-fed ewes (L, LML, HML) of our study. In vitro studies reported that although MDA can react with a broad variety of AA, the epsilon amino group of lysine is the main target [ 64 , 65 ]. Additionally, proteins compared to the free amino acids are more easily damaged by MDA under physiological conditions, as has been indicated in vitro [ 64 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…This was reported in cows [ 63 ] and lysine-fed ewes (L, LML, HML) of our study. In vitro studies reported that although MDA can react with a broad variety of AA, the epsilon amino group of lysine is the main target [ 64 , 65 ]. Additionally, proteins compared to the free amino acids are more easily damaged by MDA under physiological conditions, as has been indicated in vitro [ 64 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although this review is more focused on lipoxidation in the cellular context, protein lipoxidation in the extracellular milieu and the bloodstream has important consequences, including increased immunogenicity, transfer of proinflammatory and damage signals and contribution to a variety of pathophysiological processes [ 12 , 127 ]. In summary, lipoxidation can impact essential processes including cell signalling and metabolism, cytoskeletal function, protein degradation and gene expression.…”
Section: Functional Consequences Of Lipoxidationmentioning
confidence: 99%
“…The content of MDA can reflect the level of lipid peroxidation and the damage degree of cell lipid peroxidation to some extent. 43 Antioxidant enzymes SOD, CAT, and GSH-Px are the primary substances for scavenging free radicals in organisms, and their levels in organisms indicate an intuitive index of oxidative damage rate. 44 Most studies have shown that antioxidants are an important step in preventing aging because the build-up of ROS can lead to DNA damage, which has been shown to have a significant impact on aging.…”
Section: Discussionmentioning
confidence: 99%